The Effectiveness Of Performance- Related Pay In Increasing Employee Motivation For Greater Performance: A Case Study Of Jurong Shipyard Pte Ltd (JSPL) - Wong, Lai Cheng (2007)
The design and operation of payment systems in many organizations has often been institutionalized by custom and practice, tradition and collective bargaining mechanisms (Beardwell & Holden, 1997) and that has resulted in individuals receiving rewards that are not based on their performances or contributions but rather independently determined. However, competitive pressures have resulted in the evolution of new forms and strategies of reward management that focus particularly on performance- reward contingencies. Moving away from traditional pay systems such as seniority- based pay, payment by time, payment by output etc, organizations are now continually looking to increase their effort and performance beyond that which is at a minimally acceptable standard, or by reducing labour costs to a minimum (Beardwell & Holden, 1997; MOM, 2005 ).